CONSUMER BEHAVIOR AND DEMAND FOR HYDROPONIC VEGETABLES AT VALE FARM HYDROPONIC - Kurniawan , Shidiq; Setiyani , Rahmawati; Sepfrian , Bimoseno (LPPM Universitas Duta Bangsa Surakarta, 2023)
A healthy vegetable cultivation system using hydroponic techniques is a solution to the challenges of urban farmers, as an innovation and increase in the efficiency of the agricultural industry to meet global challenges. Vale Farm Hydroponics is an agricultural business on urban land or urban farming through a hydroponic farming system that carries the farm to table business concept, where it is possible for consumers to get a variety of good quality hydroponic vegetables directly from farmers and producers. This study uses a qualitative analysis method. Research data was obtained through interviews with 30 ValeFarm Hydroponic consumers. The survey was conducted using a questionnaire containing questions about consumer behavior and demand for hydroponic vegetables. The results of the research show that consumer behavior is divided into four stages, namely the introduction stage, the evaluation stage is influenced by various factors, such as emotional factors, rational factors, and environmental factors and the post-purchase stage. The factors that affect demand are prices of other goods, consumer income and consumer predictions about the future. The research results showed that the demand for hydroponic vegetables at Vale Farm Hydroponics was 381 kg/month.